[Rezension von: Barras, Amélie, Faith in rights : Christian-inspired NGOs at work in the United Nations] - Williams, Andrew L. (A journal of church and state, 2025)
In Faith in Rights, Amélie Barras examines the human rights advocacy of religious non-governmental organizations (NGOs) (to be abbreviated as RNGOs) to ill